Penanganan Illegal Tapping, Illegal Drilling dan Penyelewengan Bahan Bakar Minyak (BBM) Bersubsidi di Indonesia Tahun 2011-2015 - Riyandani Rahmadiah Lioty; Tri Cahyo Utomo; Shary Charlotte Pattipeilohy (Journal of International Relations Diponegoro, 2017)
Oil stealing with illegal tapping, illegal drilling and misusing of fuel subsidy mode had often occurred in the period of 2011 until 2015 in Indonesia. Indonesia incurred losses as much as ten billions every year. It was important to find out the efforts of Indonesia government because in 2011 until 2015, the number of stealing oil not only increased but also decreased. This research used qualitative method that tried to explain the efforts of Indonesia government. Furthermore, the efforts of Indonesia government were analyzed to find out the main factor why oil stealing still happened until present. The Institutional liberal theory was used for answering these phenomenon. The result showed that the efforts of Indonesia government were not enough. Indonesia government only focused on oil stealing and smuggling in domestic area, so it was the reason why oil stealing still happened in Indonesia. The international illegal oil trade syndicate that could not handle was the main reason related to oil stealing. Therefore, multilateral cooperation called institutional or regime cooperation that specifically against the international illegal oil trade syndicate was needed.